The Constitutional Court’s Systematic, Structural, and Teleological Interpretation of the Judicial Commission’s Authority and Its Implications for Judicial Independence - Pri Pambudi Teguh (Journal Evidence Of Law, 2026)
Post-amendment constitutional reform of the 1945 Constitution introduced the Judicial Commission as an independent state institution tasked with safeguarding the honor and integrity of judges. While prior studies have examined the institutional relationship between the Judicial Commission and the Supreme Court, limited attention has been given to the patterns of legal interpretation employed by the Constitutional Court in defining the Commission’s authority and their implications for the design of judicial power; this article therefore offers novelty by employing a systematic, structural, and teleological interpretative approach. This article aims to analyze the constitutional construction of the Judicial Commission’s authority from the perspective of state institutional theory and to examine the Constitutional Court’s interpretation in Decision No. 005/PUU-IV/2006, Decision No. 43/PUU-XIII/2015, and Decision No. 92/PUU-XVIII/2020, along with its implications for judicial independence. This study employs normative legal research using statutory, conceptual, and case approaches, analyzed through qualitative descriptive methods. The findings indicate that the Judicial Commission’s authority under Article 24B of the Constitution constitutes a constitutional mechanism to safeguard judicial integrity through ethical oversight and participation in the nomination of Supreme Court justices as part of a checks and balances system. Furthermore, the Constitutional Court consistently interprets this authority through systematic, structural, and teleological approaches by positioning judicial independence as the primary parameter, thereby constructing a complementary institutional relationship between the Judicial Commission and the Supreme Court in maintaining the balance between independence and accountability.